Intergenerational interaction in health promotion: a qualitative study in Brazil - Elza Maria de Souza
OBJECTIVE: In 1994 a pilot intergenerational project was started in the city of Taguatinga, Brazil, to promote the well-being of both elderly and adolescent populations using reminiscence processes as a means of interaction. The purpose of the study is to evaluate the project from the participants' viewpoint and to improve the contribution of those age groups in building up social capital. METHODS: From November 1999 to April 2000 a qualitative study using focus groups technique was conducted. Using a discussion guide, 9 groups of students, ranging in age from 13 to 19 years old, and 3 groups of elderly aged 60 years and over were interviewed to collect data regarding their interaction before and after an intergenerational program. RESULTS: The main findings suggested a change in attitude of young people toward old age and elderly people. Participating elderly people reported improvement in their health status. For both age groups the findings suggested a better understanding between generations. CONCLUSIONS: It seems that reminiscence intergenerational activity contributes to building up mutual trust and reciprocity. These results seem to indicate this is an alternative for investing in social capital and improving participants' well-being. However, further work is needed to support these findings.